(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Immunohistochemistry is any technique that can detect cellular and extracellular components in situ by means of specific antibodies, using enzymatic detection systems. Among immunohistochemical methods, the technique of avidin - biotin complex (ABC) is widely used because of its high sensitivity. The aim of this study was to evaluate the immunohistochemical reactivity of the 4C4.9 antibody for detection of S-100 protein using the ABC method. For the evaluation of immunohistochemical reactivity 2 biopsies of human skin were used with histopathological diagnosis of ulcerated malignant melanoma and melanocytic intradermal nevi from the Research Laboratory on Animal Biotechnology of the Universidad de La Frontera, Chile. The Kit VECTASTAIN® was used as detection method, the dilution the 4C4.9 antibody was 1/250 and incubation temperature was at 4 ° C or 37 °C for 18 hours. To validate the technique, a positive control and a negative for 4C4.9 was performed. The results of immunohistochemical staining by the method of ABC complex showed positive staining for protein S-100 both in ulcerated malignant melanoma and melanocytic intradermal nevi, incubated for 18 hours at 4 ° C or 37 ° C. However, immunostaining was more intense when the primary antibody was incubated at 37° C. For a correct interpretation of the results, it is necessary to take into consideration that the antigen-antibody reaction is influenced by various factors such as the concentration of antibody, time and temperature of incubation. In conclusion, our results suggest incubating the samples with the first antibody (4C4.9) at 1/250 dilution in distilled water, incubating for 18 h at 37 oC. However, immunostaining was more intense when the primary antibody was incubated at 37° C. For a correct interpretation of the results, it is necessary to take into consideration that antigen- antibody reaction is influenced by various factors such as the concentration of antibody, time and temperature of incubation. In conclusion, our results suggest incubating the samples with the first antibody (4C4.9) at 1/250 dilution in distilled water, incubating for 18 h at 37 oC. The use of the antibody 4C4.9 is recommended to support the diagnosis and differential diagnosis.